2000
DOI: 10.1111/j.1348-0421.2000.tb02513.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Sialyl Lewis X (SLe) Moiety on Splenic Accumulation of SLex‐Carboxymethylpullulan Conjugate

Abstract: Sialyl Lewis X (SLex), an E-selectin ligand, was conjugated with carboxymethylpullulan (CMPul) and the disposition characteristics of this conjugate after intravenous administration were investigated using mice with ear edema. The concentration of 3H-labeled SLex-CMPul in the spleen was significantly high. When CMPul was modified with a saccharide unable to bind to E-selectin, this splenic accumulation was not observed. The uptake of radiolabeled SLex-CMPul by the spleen was completely inhibited by a 100-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These findings are consistent with results of a study reporting that systemically administered NSCs tend to accumulate in the brains of mice with EAE, and also in the spleen and the liver (Politi et al 2007). E-selectin expression in the spleen has been described in humans, non-human primates and rodents (Redl et al 1991;Drake et al 1993;Schweitzer et al 1996;Alam et al 2000), and is upregulated by pro-inflammatory cytokines that are characteristically expressed in CNS inflammatory conditions (Weishaupt et al 2000;Emamgholipour et al 2013); indeed, conjugation of sLe x to polymers has been shown to markedly enhance the accumulation of such polymers within the spleen (Horie et al 2000(Horie et al , 2004, providing direct evidence that sLe x expression promotes splenic delivery. It has been reported that infiltration of the spleen by NSCs dampens production of inflammatory cytokines by resident spleen cells (e.g., macrophages) resulting in anti-inflammatory effects (Lee et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with results of a study reporting that systemically administered NSCs tend to accumulate in the brains of mice with EAE, and also in the spleen and the liver (Politi et al 2007). E-selectin expression in the spleen has been described in humans, non-human primates and rodents (Redl et al 1991;Drake et al 1993;Schweitzer et al 1996;Alam et al 2000), and is upregulated by pro-inflammatory cytokines that are characteristically expressed in CNS inflammatory conditions (Weishaupt et al 2000;Emamgholipour et al 2013); indeed, conjugation of sLe x to polymers has been shown to markedly enhance the accumulation of such polymers within the spleen (Horie et al 2000(Horie et al , 2004, providing direct evidence that sLe x expression promotes splenic delivery. It has been reported that infiltration of the spleen by NSCs dampens production of inflammatory cytokines by resident spleen cells (e.g., macrophages) resulting in anti-inflammatory effects (Lee et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This was the earliest time that we could find differences among CMPul conjugates in tissue distribution experiments. 5) However, CMPul conjugates were taken up by medullary sinus macrophages and a few or few silver grains were found in the marginal sinus of the lymph nodes and the vicinity of the high endothelial venules, where the influx site of lymph and the infiltration site of lymphocytes are located, respectively (Table 2). This result was almost the same as that 24 h after intravenous administration except that smaller amounts were observed.…”
Section: Uptake Of 2-3slementioning
confidence: 99%
“…5) We tried to verify whether this accumulation of 2-3SLe x -CMPul in the spleen was dependent on the number (d.s.) of 2-3SLe…”
Section: Uptake Of 2-3slementioning
confidence: 99%
See 1 more Smart Citation